The hotel industry in service economies: from one ''service world'' to another. (1st April 2010) - ,; ,
Abstract : Rethinking national models in order to render them capable of taking account of the sectoral dimensions of employment systems is the central issue addressed in this paper. The ''service worlds'' approach, based on an analysis of economic and social conventions, is one possible avenue to be taken in search of a solution. Drawing on empirical research on hotel services, this article draws three main conclusions. First, it shows that conventions and power relations are structured by the interplay of numerous forces at work at a sectoral level that until now have led to tacit agreements between governments and employers in which the volume of jobs created has taken precedence over the quality of those jobs. Second, it demonstrates that the logics that structure global, national, sectoral and corporate spaces, such as outsourcing, vertical integration and particular employment forms, are mingled and intertwined. Finally, it identifies tangible or symbolic connectors that facilitate movement between the global, national, sectoral and corporate spaces and which open up or, conversely, close off the boundaries of these spaces to new logics. Interacting with national models whilst simultaneously minimising their importance, they are helping to shift services from one world to another.